2012
DOI: 10.1186/1471-2164-13-s8-s14
|View full text |Cite
|
Sign up to set email alerts
|

Differential combinatorial regulatory network analysis related to venous metastasis of hepatocellular carcinoma

Abstract: BackgroundHepatocellular carcinoma (HCC) is one of the most fatal cancers in the world, and metastasis is a significant cause to the high mortality in patients with HCC. However, the molecular mechanism behind HCC metastasis is not fully understood. Study of regulatory networks may help investigate HCC metastasis in the way of systems biology profiling.MethodsBy utilizing both sequence information and parallel microRNA(miRNA) and mRNA expression data on the same cohort of HBV related HCC patients without or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 46 publications
2
29
0
Order By: Relevance
“…Downregulation of miR-204 is a frequent event in several cancers [20,21,22,23,24,25]. Recently, mounting evidence indicate that miR-204 play crucial roles in tumor invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Downregulation of miR-204 is a frequent event in several cancers [20,21,22,23,24,25]. Recently, mounting evidence indicate that miR-204 play crucial roles in tumor invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…miR-204 has been shown to be down-regulated and serve as a potential tumor suppressor in several distinct cancer types including endometrial cancer, malignant peripheral nerve sheath tumors, gastric cancer, glioma, and hepatocellular carcinoma [20,21,22,23,24,25]. However, the role of miR-204 in ICC progression and the molecular mechanisms by which miR-204 exerts its functions remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Only two previous papers have speculated about the role of miR-16 expression in HCC: Qu et al [27] reported significantly lower levels of this microRNA in the serum of HCC patients compared to controls, while Zeng et al [28] attributed to it the ability of HCC to generate metastasis through repression of NOTCH signaling cascade. The data about the miR-16/HCC issue are scarce and conflicting, and we could not confirm any of the previously described scenarios since no aberrant expression of miR-16 was detected in our HCC cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The authors showed that BCmicrO could outperform each individual algorithm measured by both sensitivity and specificity. Zeng et al, [19] demonstrated an integrative approach to studying differential combinatorial regulatory networks in venous metastasis of hepatocellular carcinoma. Both the microRNA and transcription factor regulations are integrated in their network analysis.…”
Section: Bmc Genomics Supplement Issuementioning
confidence: 99%